2010
DOI: 10.1111/j.1750-3639.2009.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Inhibitor of Growth (ING‐4) is Implicated in the Pathogenesis and Progression of Human Astrocytomas

Abstract: Inhibitor of growth 4 (ING-4) is a tumor suppressor gene that interacts with nuclear factor-kappaB (NF-kappaB) and represses its transcriptional activity. Several lines of evidence suggest that the tumor suppressor gene ING-4, the transcription factor NF-kappaB and its target genes matrix metalloproteases MMP-2, MMP-9 and urokinase plasminogen activator (u-PA) are critically involved in tumor invasion. The aim of the present study was to investigate immunohistochemically the expression pattern of ING-4, NF-kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…To the best of our knowledge, no study has investigated the level of expression of ING4 in human osteosarcoma tissue as compared with normal bone tissue, or the prognostic value of ING4 expression in patients diagnosed with osteosarcoma. Similar to the results of previous studies regarding other malignant tumors (11,18,20,(28)(29)(30)(31), the results of the present study demonstrated that the osteosarcoma tissues had significantly decreased expression of ING4 when compared with the normal bone tissues (P<0.001). The majority of the osteosarcoma specimens had a score of (-) or (+), whilst no normal bone specimens had a score of (-) or (+).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…To the best of our knowledge, no study has investigated the level of expression of ING4 in human osteosarcoma tissue as compared with normal bone tissue, or the prognostic value of ING4 expression in patients diagnosed with osteosarcoma. Similar to the results of previous studies regarding other malignant tumors (11,18,20,(28)(29)(30)(31), the results of the present study demonstrated that the osteosarcoma tissues had significantly decreased expression of ING4 when compared with the normal bone tissues (P<0.001). The majority of the osteosarcoma specimens had a score of (-) or (+), whilst no normal bone specimens had a score of (-) or (+).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have demonstrated that ING4 expression is suppressed or reduced in a number of malignancies, and the degree of expression is associated with the tumor grade (11,18,20,(28)(29)(30)(31). To the best of our knowledge, no study has investigated the level of expression of ING4 in human osteosarcoma tissue as compared with normal bone tissue, or the prognostic value of ING4 expression in patients diagnosed with osteosarcoma.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations